Digital media and political engagement worldwide : a comparative study - Anduiza Perea, Eva.; Jensen, Michael James; Jorba, Laia. (New York : Cambridge University Press, 2012)
'This book explores how digital media use affects political attitudes and behavior, and how this relationship is shaped by political environments across countries'--
'This book focuses on the impact of digital media use for political engagement across varied geographic and political contexts, using a diversity of methodological approaches and datasets. The book addresses an important gap in the contemporary literature on digital politics, identifying context dependent and transcendent political consequences of digital media use. While the majority of the empirical work in this field has been based on studies from the United States and United Kingdom, this volume seeks to place those results into comparative relief with other regions of the world. It moves debates in this field of study forward by identifying system-level attributes that shape digital political engagement across a wide variety of contexts. The volume brings together research and scholars from North America, Europe, Latin America, the Middle East, and Asia. The evidence analyzed across the fifteen cases considered in the book suggests that engagement with digital environments influences users' political orientations and that contextual features play a significant role in shaping digital politics'--
Includes bibliographical references (p. 253-282) and index.
Includes bibliographical references and index.
Keywords: Political participation -- Technological innovations -- Cross-cultural studies; Communication in politics -- Technological innovations -- Cross-cultural studies; Internet -- Political aspects -- Cross-cultural studies